EXPLORING POLITICAL CONFLICT AND METADRAMA IN CAROL CHURCHILL’S WORKS: A THEATRICAL RESPONSE TO GLOBAL CRISES - Iskandarova Navbakhor Ilkhomovna (XALQARO ILMIY-AMALIY ANJUMAN "TA’LIM MAYDONI TENDENSIYALARI: KOMPETENTSIYALAR, INNOVATSIYALAR VA TEXNOLOGIYALAR", 2025)
This article examines the representation of political conflicts in the plays of Carol Churchill, focusing on her unique approach to political theater. Churchill’s works, such as Mad Forest, Far Away, and Seven Jewish Children, respond to pressing political issues, including the Romanian revolution, the Bosnian conflict, and the Middle Eastern strife. Central to her political dramaturgy is the use of metadrama, which allows Churchill to intertwine artistic representation with real-world events, creating an intellectual dialogue with her audience. Drawing on Brechtian principles, Churchill’s theater challenges traditional narratives by incorporating complex social and political dynamics. The article explores how Churchill’s works engage with the epistemological and ontological dimensions of theater, particularly in Mad Forest, which emerges from a collective creation process that involved Romanian and British participants.